Marketing Strategy for Lely Gorden Interior MSME Using SOAR Analysis and Quantitative Strategic Planning Matrix (QSPM) - I Gusti Ayu Sri Deviyanti; Moh. Ainul Fais; Nyoman Sri Widari; Suhatati Tjandra; Endang Sriwahyuni (Jurnal Optimalisasi, 2026)
Competition among interior-related MSMEs requires marketing strategies that connect internal capability with market opportunity. Previous studies have discussed MSME marketing strategies using SWOT, SOAR, and QSPM, but limited attention has been given to interior curtain MSMEs that rely on customization, product quality, installation service, and customer trust. This study aims to formulate and determine the priority marketing strategy for Lely Gorden Interior MSME by integrating SOAR analysis and the Quantitative Strategic Planning Matrix (QSPM). This research used a descriptive case study approach. Primary data were obtained through owner interviews and field observation, while secondary data were collected from business documents and relevant literature. The data were analyzed using SOAR, EFE, IFE, IE, and QSPM matrices. The EFE and IFE scores were 3.60 and 3.40, placing the MSME in Quadrant I of the IE matrix. This position indicates a growth-oriented strategy. The SOAR matrix produced four alternative strategies. QSPM results show that building a premium brand image through customized product quality and personalized service across online and offline channels obtained the highest Total Attractiveness Score of 3.70. The study contributes to MSME strategy literature by showing how SOAR and QSPM can convert qualitative business potential into measurable marketing priorities in an interior MSME context.